The new Dutch "slapskates": Will they revolutionize speed skating technique - Seiler, S.
As an initial test, van Ingen Schenau's group employed skaters from the pool of junior skating talent in the Netherlands. Eleven junior skaters (14-18 y) agreed to switch to the slapskates for the 94/95 season. Their performance progression was compared with 72 "normal" skaters in the same region by using the official ranking lists of the Royal Dutch Speed Skating Association. Comparing seasonal results, the slapskaters improved their performances by an average of 6.2%, compared to 2.5% for the normal skaters. Moreover, while the highest regional rankings for the new slapskaters in the previous season had been 36, 11, and 8th in respective age groups, slapskaters led all three lists by the end of the test season. Two of these three went on to win the Dutch national all-around championships for their age-group. From on analysis of individual events, it appeared that slapskates had a relatively greater impact on distance performances than sprint performances. The non-linear power-velocity relationship that applies to overcoming air friction may explain this difference. Overall the data left little doubt that slapskates were positively impacting performance.